Reducing sedentary time using an innovative mHealth intervention among patients with total knee replacement: Rationale and study protocol - Pellegrini, Christine A. (Contemp Clin Trials Commun, 2021)
INTRODUCTION: Although knee replacement is effective for improving pain and physical function, subsequent improvements in physical activity typically do not follow. As a result, many patients spend most of their day engaged in sedentary behavior, which may put them at higher risk of experiencing poor function and disability. Intervening on sedentary time, rather than physical activity, may be a more feasible first-step approach for modifying activity-related behaviors in adults who received knee replacement. OBJECTIVE: The purpose of this study is to examine the use of a mobile health (mHealth) intervention to reduce sedentary time among adults who received a knee replacement at 3 and 6 months after surgery. METHODS: Patients (n = 92) scheduled for knee replacement will be recruited and at 4 weeks after surgery, they will be randomized to either NEAT!2 or Control. NEAT!2 participants will use the NEAT!2 smartphone app, which provides a vibration and/or audible tone to interrupt prolonged bouts of sitting detected from the smartphone's internal accelerometer, until 3 months after surgery. NEAT!2 participants will receive biweekly coaching calls between 4 and 12 weeks after surgery. Control participants will receive an education control app and receive non-intervention calls to assess general surgery recovery. Both groups will receive 3 retention calls between 3 and 6 months. Data collection will occur pre-operatively and at 3 and 6 months after surgery. DISCUSSION: The results of this study will help to determine whether an innovative remotely-delivered, mHealth sedentary reduction intervention can decrease sedentary time in adults after knee replacement.